Study of the stability of organoleptic and structural-mechanical indicators of semi-solid preparations with metal nanoparticles - Bilous, Svіtlana; Kovalevskaya, Inna (ScienceRise: Pharmaceutical Science, 2019)
Aim. Research of the stability of organoleptic and rheological properties of semi-solid preparations with silver and gold nanoparticles. Methods. For the study of organoleptic parameters, a classic method for determining the stability with periodic control of dosage forms in two temperature regimens was used: 8-15 °C (cool place) and 15-25 °C (room temperature). To study the rheological characteristics of semi-solid preparations, a rotary viscometer with a system of coaxial cylinders was used. Results. We studied three medicinal forms based on silver nanoparticles - ointment, cream and gel, which can be promising for the use in dermatology, as well as two dosage forms based on nanoparticles of silver and gold for the use in dentistry and surgery for the treatment of infectious, purulent-inflammatory diseases of skin and mucous membranes of the oral cavity. Within 24 month of storage of dosage forms in a dark place in dark glass containers every 6 months the following parameters: homogeneity, odour, colour and pH were monitored. Rheological parameters were investigated after the preparation of dosage forms and after 24 months of storage. According to the rheological indicators rheograms of stream semi-solid preparations were constructed, and also indicators of mechanical stability were calculated. It was found that all samples are coagulation systems with a pseudoplastic flow type. The obtained rheograms contain loops of hysteresis, which characterize their certain degree of thixotropy. Conclusion. According to the results of studies the stability of organoleptic characteristics of semi-solid preparations at a storage temperature 8-15 0С in a place protected from light is established. According to the rheological properties, samples of studied semi-solid preparations have a good ability to apply on the skin and extrusion from tubes.